Booked [large type] - Alexander, Kwame (Alexander, Kwame. Crossover series, 2020)
"In this follow-up to Newbery-winner THE CROSSOVER, soccer, family, love, and friendship take center stage. Twelve-year-old Nick learns the power of words as he wrestles with problems at home, stands up to a bully, and tries to impress the girl of his dreams. Helping him along are his best friend and sometimes teammate Coby, and The Mac, a rapping librarian who gives Nick inspiring books to read. This electric and heartfelt novel-in-verse by poet Kwame Alexander bends and breaks as it captures all the thrills and setbacks, action and emotion of a World Cup match!"--Back cover